Genetics Landscape of Nonsyndromic Hearing Loss in Indian Populations - Ray, Manisha; Sarkar, Saurav; Sable, Mukund Namdev (Journal of Pediatric Genetics, 2021)
Congenital nonsyndromic hearing loss (NSHL) has been considered as one of the most prevalent chronic disorder in children. It affects the physical and mental conditions of a large children population worldwide. Because of the genetic heterogeneity, the identification of target gene is very challenging. However, gap junction β-2 (GJB2) is taken as the key gene for hearing loss, as its involvement has been reported frequently in NSHL cases. This study aimed to identify the association of GJB2 mutants in different Indian populations based on published studies in Indian population. This will provide clear genetic fundamental of NSHL in Indian biogeography, which would be helpful in the diagnosis process.
Keywords: nonsyndromic hearing loss; genetics; GJB2; India; mutation